2017
DOI: 10.1007/s11121-017-0799-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception, Sexual Behaviors, and PrEP Adherence Among Substance-Using Men Who Have Sex with Men: a Qualitative Study

Abstract: The antiretroviral drug combination emtricitabine and tenofovir disoproxil fumerate (TDF/FTC) taken as preexposure prophylaxis (PrEP) is effective in preventing HIV infection, yet it also requires adherence and potentially decreases condom use. This study sought to examine these issues among a key population at risk for HIV, substance-using men who have sex with men (MSM). We conducted semi-structured interviews with an ethnically diverse sample of 30 young (aged 20–35) MSM prescribed PrEP within a large integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 44 publications
6
78
1
Order By: Relevance
“…Additionally, our results reinforce and expand on previous studies that have started to demonstrate the individual positive outcomes of PrEP use beyond biomedical outcomes (Grant & Koester, 2016). For instance, previous qualitative research reported relief from stress and fear associated with PrEP use among participants in clinical trials, substance-using men who have sex with men (MSM), and MSM in Seattle (Collins et al, 2017;Koester et al, 2017;Storholm et al, 2017). Furthermore, a previous study of real-world patient experiences identified increased HIV and STI screening as a frequent outcome of PrEP adoption (Parker et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Additionally, our results reinforce and expand on previous studies that have started to demonstrate the individual positive outcomes of PrEP use beyond biomedical outcomes (Grant & Koester, 2016). For instance, previous qualitative research reported relief from stress and fear associated with PrEP use among participants in clinical trials, substance-using men who have sex with men (MSM), and MSM in Seattle (Collins et al, 2017;Koester et al, 2017;Storholm et al, 2017). Furthermore, a previous study of real-world patient experiences identified increased HIV and STI screening as a frequent outcome of PrEP adoption (Parker et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…In our and other studies, PrEP stigma is closely tied to stigma around HIV, "risky" sexual behavior, and sexual and gender identity (Franks et al, 2018;Grace et al, 2018;Haire, 2015). Just as we found, other researchers have observed that stigma can be an obstacle to PrEP use, but that PrEP is also an opportunity to expose and combat stigma around HIV and sexuality (Grace et al, 2018;Storholm et al, 2017). Additionally, we noted, as did others, that PrEP users had a sense of pride around PrEP (Grace et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Routine HIV testing, keeping HIV-infected PWID virally suppressed, and efforts to diminish injection drug use are also essential components of HIV prevention efforts in this population. MSM who use methamphetamine remain a priority population for HIV pre-exposure prophylaxis (PrEP), yet PrEP use and adherence in this population can be challenging (Storholm et al, 2017). Data from the present study suggest that non-MSM who inject methamphetamine may also benefit from PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…While there are data on the motives to use daily PrEP , little is known about the reasons to choose between daily and event‐driven PrEP, to switch between these regimens, or to discontinue PrEP use altogether in a setting that offers both regimens. The majority of previous studies reported on situations in which event‐driven PrEP was only a hypothetical option , and where stops were associated with daily adherence problems and reduced risk . Data on actual choices between daily and event‐driven PrEP among MSM are only available from three studies in the European setting, the roll‐out programme in France , the Be‐Prepared study in Belgium , and our own study, the Amsterdam PrEP (AMPrEP) demonstration project in the Netherlands .…”
Section: Introductionmentioning
confidence: 99%